EVALUATION OF BIOCHEMICAL MARKERS OF BONE TISSUE METABOLISM WHEN USING OSTEOTROPIC MATERIAL IN DENTAL IMPLANTATION - Mannanov Javlonbek Jamoliddinovich; Rejabboeva Navruza Komiljon kizi; Khalmatova Matlyuba Artykovna (Scholar Express Journals, 2025)
Optimization of osseointegration conditions in dental implantation by introducing calcium-based bone tissue regeneration stimulants into the body to improve the effectiveness of treatment of patients with dental defects
Keywords: Dental Implantation; Dental Defects